2017
DOI: 10.1016/j.expneurol.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Ventral medullary control of rapid eye movement sleep and atonia

Abstract: Discrete populations of neurons at multiple levels of the brainstem control rapid eye movement (REM) sleep and the accompanying loss of postural muscle tone, or atonia. The specific contributions of these brainstem cell populations to REM sleep control remains incompletely understood. Here we show in rats that viral vector-based lesions of the ventromedial medulla at a level rostral to the inferior olive (pSOM) produced violent myoclonic twitches and abnormal electromyographic spikes, but not complete loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…And while there is ample evidence to support this view, it is important to bear in mind that both old and recent studies have inferred the existence of at least one additional region that is important for REM sleep control. Specifically, outcomes of lesion, unit recording and chemogenetic studies have suggested an important role for the vM, including the medially located ventral gigantocellular reticular nucleus (GiV) and α-gigantocellular reticular nuclei (GiA) and laterally adjacent paragigantocellular (LPGi) cell groups, in REM sleep control and REM sleep atonia [8,107109]. In general support of this concept, a recent optogenetic study found that activation of vM GABA neurons could potently trigger REM sleep and produce REM sleep atonia, and that this effect was likely mediated through the vlPAG-SLD circuit and direct, i.e., SLD-independent, projections to spinal motor neurons [13].…”
Section: Brain Circuitry Controlling Rem Sleepmentioning
confidence: 99%
“…And while there is ample evidence to support this view, it is important to bear in mind that both old and recent studies have inferred the existence of at least one additional region that is important for REM sleep control. Specifically, outcomes of lesion, unit recording and chemogenetic studies have suggested an important role for the vM, including the medially located ventral gigantocellular reticular nucleus (GiV) and α-gigantocellular reticular nuclei (GiA) and laterally adjacent paragigantocellular (LPGi) cell groups, in REM sleep control and REM sleep atonia [8,107109]. In general support of this concept, a recent optogenetic study found that activation of vM GABA neurons could potently trigger REM sleep and produce REM sleep atonia, and that this effect was likely mediated through the vlPAG-SLD circuit and direct, i.e., SLD-independent, projections to spinal motor neurons [13].…”
Section: Brain Circuitry Controlling Rem Sleepmentioning
confidence: 99%
“…Our previous work in rodents has suggested that dysfunction of pontine and medullary reticulospinal systems that support normal REM sleep atonia may underlie RLS. However, lesions of these structures that are sufficient to disturb motor activity during REM sleep do not alter motor activity during NREM sleep and sleep-wake transition periods 8 11 . Thus supra-pontine structures with direct projections to the spinal cord may play a more critical role in RLS, including the corticospinal tract, rubrospinal tract and hypothalamic A11 dopaminergic cell group.…”
Section: Introductionmentioning
confidence: 99%
“…And similar to the identification and characterization of the SWS-promoting PZ, technical advances have enabled a more refined understanding of the cellular and synaptic basis by which a distributed network of brainstem circuits regulation REM sleep, including the recent identification of GABAergic REM-generator cells in the ventral medulla [42-45]. …”
Section: Introductionmentioning
confidence: 99%